Molecular clouds and star formation proceedings of the 7th Guo Shoujing Summer School of Astrophysics, Wuxi, China, 30 June-5 July 1993 - Yuan, Chi; You, Junhan (World Scientific, 2014)
"This volume is composed of four major in-depth yet pedagogic review chapters on the subject of star formation, written by the foremost researchers in the field. Recent infrared and millimeter radio observations are respectively reviewed by Charlie Lada and Phil Myers, both of Harvard-Smithsonian Center for Astrophysics. The theoretical work is reviewed by Frank Shu of UC-Berkeley on the gravitational collapse of dense cores in a giant molecular cloud to form sunlike stars and Bruce Elmegreen of IBM-Watson on the gravitational instability, leading to large-scale star formation. They have written at a level most suitable for graduate students or young researchers who want to develop their research interest in the field, with the most complete literature survey to date. This volume is not an ordinary conference proceedings, but a textbook to be used in graduate study in astrophysics. The volume also includes other short and interesting contributions from Doug Lin of UC-Santa Cruz, Paul Ho of Harvard-Smithsonian, Masa Hayashi of Tokyo University, Debra Elmegreen of Vassar, Jing-Yao Hu of Beijing Observatory, Guo-Xuan Sung of Shanghai Observatory, Chi Yuan of CCNY and ASIAA, and Wen-Ping Chen of Central University, Taiwan."--Publisher's description